Establishing and sustaining a virtual community of practice to enhance nurses’ research knowledge and skills: An action research study from the United Arab Emirates - Nabeel Al Amiri; Khaled Al Qawasmeh (Journal of Healthcare Administration)
Background: A Community of Practice (CoP) is a professional learning and development approach that facilitates knowledge sharing, skill enhancement, and collaboration among individuals within the same profession. It is typically structured around regular meetings focused on achieving a shared professional goal.